Pengaruh Kecerdasan Spiritual, Intelektual, dan Emosional terhadap Pengelolaan Keuangan Pribadi Mahasiswa dengan Moderasi Peer Group - Cahyapuspita, Hizkisevia Ayu; Rita, Maria Rio (Business Education Program of Universitas Pendidikan Indonesia, 2022)
This study aims to determine the factors that can affect the personal financial management of Satya Wacana Christian University Faculty of Economics and Business students such as spiritual, intellectual, and emotional intelligence moderated by peer groups. The analysis technique used in this research is SEM-PLS using the Smart PLS 3.0 program. This study states that spiritual and intellectual intelligence has a significant positive effect, while emotional intelligence has a significant negative effect. The role of the peer group as a moderator in this study shows that the peer group does not strengthen or weaken the spiritual, intellectual, and emotional intelligence variables on personal financial management.